EBRO 1938. History, archeology and teaching of an aerial battle - Hernández Cardona, Xavier; Íñiguez Gracia, David; Sospedra Roca, Rafel (Clio. History and History Teaching, 2020)
The Battle of the Ebro (1938) faced people and machines for 115 days. New techniques and technologies were experimented with that would play a determining role in the impending world conflict. Aviation was used, for the first time, on a massive scale and its performance was decisive. However, its heritage and trace is scarce. In the environment of the air war in the Battle of the Ebro, this work presents a cross-sectional and holistic research experience that raises the didactic socialization of historical and archaeological knowledge based on museographic methodological proposals, didactic iconography and the recovery of historical memory. The objective of this combined action is to generate and socialize scientific knowledge about the past and its material legacy, influence the formation of a critical citizenry and promote sustainable economic development based on the action of cultural industries related to heritage.